Endothelial ACKR3 drives atherosclerosis by promoting immune cell adhesion to vascular endothelium. (10th June 2022) - Van Der Vorst, E; Gencer, S; Jansen, Y; Bayasgalan, S; Yan, Y; Bianchini, M; Cimen, I; Mueller, M; Peters, L; Megens, R; Duchene, J; Lemnitzer, P; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): Deutsche Forschungsgemeinschaft SFB1123 European Research Council AdG_692511 Background: Genome wide association studies revealed a strong association between the CXCL12 gene locus and cardiovascular diseases, highlighting its receptors CXCR4 and atypical chemokine receptor-3 (ACKR3) as targets for CVD research. Although vascular CXCR4 is well studied in atherosclerosis, the exact role of ACKR3 remains elusive. Therefore, the aim of this project is to decipher the role of vascular ACKR3 in atherosclerosis. Methods: Vascular endothelium (Bmx-cre) specific Ackr3 deficient mice on Apoe-/- background were fed with a cholesterol-rich diet. Lesions in the aortic roots and arches were analyzed via H&E staining. The phenotype was further characterized employing ex-vivo perfusion and intravital microscopy for cell adhesion and Evans-blue injection for endothelial permeability. Signaling studies are performed in human coronary artery endothelial cells (HCAECs). Results: Endothelial Ackr3 deficiency resulted in significantly smaller atherosclerotic lesions, accompanied by a more stable plaque phenotypes (more lesional collagen and smooth muscle cell content, smaller necrotic cores). Endothelial-Ackr3-/- mice revealed a reduction in plaque macrophage content and ICAM positive endothelial cells in atherosclerotic lesions. Moreover, immune cell adhesion on carotid arteries lacking endothelial ACKR3 was decreased whilst endothelial permeability was not affected. ACKR3 silencing in TNF-stimulated HCAECs decreased adhesion molecule expression and downregulated MAPK signaling and NF-kB p65 phosphorylation. Endothelial cells in atherosclerotic lesions also revealed decreased phospho-NF-kB p65 expression in Ackr3 deficient mice. Conclusion: Collectively, our findings indicate that arterial endothelial ACKR3 fuels atherosclerosis by mediating endothelium-immune cell adhesion, most likely through inflammatory MAPK and NF-kB pathways resulting in increased adhesion molecule expression.